Superior removal of inorganic and organic arsenic pollutants from water with MIL-88A(Fe) decorated on cotton fibers - Da Pang; Chong-Chen Wang; Peng Wang; Liu, Wen; Huifen Fu; Chen Zhao (Chemosphere, 2020)
Arsenic contamination has attracted worldwide concerns, owing to its toxicity and severe threat to human and environment. It is urgent to develop efficient adsorbents to remove arsenic pollutants. Within this paper, both pristine MIL-88A(Fe) and MIL-88A(Fe) decorated on cotton fibers were successfully fabricated using an eco-friendly method. The pristine MIL-88A(Fe) displayed outstanding adsorption performances towards four selected arsenic pollutants, in which the adsorption capacities toward As(III), As(V), ROX and ASA were 126.5, 164.0, 261.4 and 427.5 mg g−1, respectively. Additionally, MIL-88A(Fe) exhibited excellent removal efficiencies in a wide pH range and with the presence of different co-existing ions. It was proposed that the coordinative interactions of As–O–Fe between arsenic pollutants and MIL-88A(Fe) contributed to the superior adsorption performances. Furthermore, two MIL-88A(Fe)/cotton fibers composites were synthesized by both post synthesis (MC-1) and in-situ synthesis (MC-2), which demonstrated identically outstanding adsorption activities toward four selected arsenic pollutants. MC-1 and MC-2 enhanced the stability and reusability of MIL-88A(Fe), which was challenging issues of pristine MIL-88A(Fe) powder. Additionally, the fixed-bed column packed by MC-1 or MC-2 can continuously eliminate arsenic pollutants from the water flow. This work provided a new possibility of metal-organic frameworks to accomplish potentially large-scale application to purify the arsenic-contaminated water.
Keywords: Adsorptive removal; Cotton fibers; Inorganic arsenics; MIL-88A(Fe); Organic arsenics